1982
DOI: 10.1007/bf01544989
|View full text |Cite
|
Sign up to set email alerts
|

Sexual life of women with the Küstner-Rokitansky syndrome

Abstract: The sexual development and sex life of 12 women with the Küstner-Rokitansky syndrome, in whom the developmental anomaly (vaginal agenesis) was corrected through surgery, were examined through structured interviews and by means of questionnaires. The comparison group was 22 women who had regular menses and a functional sex life. All differences between the groups were statistically nonsignificant. Only in one questionnaire was there a slight trend toward retarded heterosexual development in the patient sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 3 publications
0
5
0
2
Order By: Relevance
“…Three studies indicated sexual dysfunction in some of the patients and their partners when assessed shortly after diagnosis or medical treatment, including anorgasmia, dyspareunia, and erectile problems in partners (Freundt et al, 1993;Mobus et al, 1996;Poland & Evans, 1985). However, studies have also determined that long-term sexual functioning in post-treatment patients is generally similar to that of young women without the disorder (Communal, Chevret-Measson, Golfier, & Raudrant, 2003;Freundt et al, 1993;Hecker & McGuire, 1977;Klingele et al, 2003;Langer et al, 1990;Poland & Evans, 1985;Raboch & Hořejší, 1982). Qualitative and case study research has generally revealed a mixture of both positive and negative attitudes towards sexuality and partnership issues among patients with vaginal agenesis (Coney, 1992;David, Toullalan, Besse, Potiron, & Delga, 1975;Holt & Slade, 2003;Kaplan, 1968;Langer et al, 1990;Poland & Evans, 1985).…”
Section: Introductionmentioning
confidence: 94%
“…Three studies indicated sexual dysfunction in some of the patients and their partners when assessed shortly after diagnosis or medical treatment, including anorgasmia, dyspareunia, and erectile problems in partners (Freundt et al, 1993;Mobus et al, 1996;Poland & Evans, 1985). However, studies have also determined that long-term sexual functioning in post-treatment patients is generally similar to that of young women without the disorder (Communal, Chevret-Measson, Golfier, & Raudrant, 2003;Freundt et al, 1993;Hecker & McGuire, 1977;Klingele et al, 2003;Langer et al, 1990;Poland & Evans, 1985;Raboch & Hořejší, 1982). Qualitative and case study research has generally revealed a mixture of both positive and negative attitudes towards sexuality and partnership issues among patients with vaginal agenesis (Coney, 1992;David, Toullalan, Besse, Potiron, & Delga, 1975;Holt & Slade, 2003;Kaplan, 1968;Langer et al, 1990;Poland & Evans, 1985).…”
Section: Introductionmentioning
confidence: 94%
“…Dem entspricht auch das Ergebnis von Giannesi und Kollegen (2005), die bei einem Vergleich der FSFI-Werte von Frauen mit MRKH und einer Kontrollgruppe keinen Unterschied fanden. Ebenso wurden zwischen Frauen mit MRKH und einer Kontrollgruppe keine Unterschiede bezüglich sexueller Entwicklung, Aktivität und Erregbarkeit (Raboch et al 1982), bezüglich des Sexualverhalten (Möbus et al 1996) sowie hinsichtlich sexueller Vorstellungen (Lewis et al 1983) berichtet. Auch Brun et al (2002) fanden in ihrer Fragebogenerhebung zur Sexualität keinen Unterschied zwischen Frauen mit MRKH und einer Kontrollgruppe.…”
Section: Sexualitätunclassified
“…We received 27 of 37 (73%) mailed questionnaires; the mean patient age at the time of analysis (March 2000) was 22 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) years and the mean time from CVP was 8.5 (0.1-18) years. The results are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%